Funds of knowledge : theorizing practices in households, communities, and classrooms - González, Norma; Moll, Luis C.; Amanti, Cathy (Lawrence Erlbaum Associates, Publishers, 2009)
"The concept of 'funds of knowledge' is based on a simple premise: people are competent and have knowledge, and their life experiences have given them that knowledge. The claim in this book is that first-hand research experiences with families allow one to document this competence and knowledge, and that such engagement provides many possibilities for positive pedagogical actions. Drawing from both Vygotskian and neo-sociocultural perspectives in designing a methodology that views the everyday practices of language and action as constructing knowledge, the funds of knowledge approach facilitates a systematic and powerful way to represent communities in terms of the resources they possess and how to harness them for classroom teaching. This book accomplishes three objectives: It gives readers the basic methodology and techniques followed in the contributors' funds of knowledge research; it extends the boundaries of what these researchers have done; and it explores the applications to classroom practice that can result from teachers knowing the communities in which they work"--Provided by publisher.